Scientific and organisational activity of Soviet researchers for the preparation of the historical atlas of the USSR in the 1960s – early 1980s - Kholmatov, Temurmalik K. (Journal of the Belarusian State University. History, 2024)
Based on office materials from the Archive of the Russian Academy of Sciences and the Scientific Archive of the Institute of Russian History of the Russian Academy of Sciences, the scientific and organisational activities of Soviet researchers during the preparation of the historical atlas of the USSR in the 1960s and early 1980s are reconstructed. It is noted that a historical geography group of the USSR was created at the Institute of History of the Academy of Sciences of the USSR to implement this project. Close attention is paid to the obstacles faced by specialists in the process of working on the project. The main problems were related to the shortage of personnel and difficulties in coordinating scientific activities. It is concluded that, given the scale and complexity of the work, the shortage of personnel, primarily cartographers and specialists in historical geography of certain regions of the USSR, forced researchers to turn to colleagues not only from other institutes of the Academy of Sciences of the USSR and central scientific and educational institutions, but also from the academies of sciences of the union republics. In the late Soviet years, the deadlines for the creation of the atlas were repeatedly postponed, as a result, the project was never implemented. Despite this, the work carried out played a major role in the development of historical and geographical research in the USSR.